2023
DOI: 10.1177/15394492231153113
|View full text |Cite
|
Sign up to set email alerts
|

An Occupation-Based Healthy Nutrition and Wellness Program for Individuals With Schizophrenia

Abstract: This study investigated the effectiveness of an occupation-based Healthy Nutrition and Wellness Program (HNWP) on dietary knowledge, dietary habits, metabolic values, and well-being of people with schizophrenia. Forty clients attended the HNWP once a week for 12 weeks in addition to routine treatment. Metabolic values, biochemical values, dietary habits, Healthy Nutrition Knowledge Form, and Well-being Questionnaire were measured before the HNWP, after the HNWP, and at 6-month follow-up. Repeated measures fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Furthermore, academic disadvantage and unemployment in schizophrenia are all part of a vicious cycle that frequently results in poor academic performance and joblessness. 21 , 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, academic disadvantage and unemployment in schizophrenia are all part of a vicious cycle that frequently results in poor academic performance and joblessness. 21 , 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…Considering that medications often show limited effectiveness in treating NS and cognitive deficits in SCZ, which substantially impact patients’ quality of life. 38 There are also no pharmacological therapies currently approved specifically for the treatment of negative symptoms, 39 and advances in conceptualisation and evaluation have not yet been fully reflected in treatment studies, 40 many of which have found that cognitive remediation can produce meaningful benefits in terms of cognition and function. 41 , 42 …”
Section: Discussionmentioning
confidence: 99%
“…Likewise, tests that measure functioning and quality of life more specifically, but also as a self-assessment by the patients themselves, could be useful in the continuation of treatment and its monitoring. 35 …”
Section: Discussionmentioning
confidence: 99%